2022
DOI: 10.3390/app12115499
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Analysis of Intelligence-Based Pathfinding Algorithms in the Field of Video Games

Abstract: This paper provides a performance comparison of different pathfinding Algorithms used in video games. The Algorithms have been classified into three categories: informed, uninformed, and metaheuristic. Both a practical and a theoretical approach have been adopted in this paper. The practical approach involved the implementation of specific Algorithms such as Dijkstra’s, A-star, Breadth First Search, and Greedy Best First. The comparison of these Algorithms is based on different criteria including execution tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…These search techniques or algorithms are typically utilized by intelligent agents in AI to solve certain problems and deliver the best outcomes [ 27 ]. There are mainly three types of algorithms: deterministic algorithms, non-deterministic algorithms, and procedural generation algorithms [ 28 ]. The categorization of AI algorithms is shown in Fig.…”
Section: Methods Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…These search techniques or algorithms are typically utilized by intelligent agents in AI to solve certain problems and deliver the best outcomes [ 27 ]. There are mainly three types of algorithms: deterministic algorithms, non-deterministic algorithms, and procedural generation algorithms [ 28 ]. The categorization of AI algorithms is shown in Fig.…”
Section: Methods Detailsmentioning
confidence: 99%
“…CEO David Helgason defines Unity as “a toolset used to build applications, and it is the technology that executes the graphics, the audio, the physics, the interactions, and the networking” [ 28 ]. Unity 3D is an Integrated Development Environment (IDE) and game engine for developing interactive media, primarily video applications.…”
Section: Methods Detailsmentioning
confidence: 99%
“…Some examples are Dijkstra, Shortest Path, Breadth Search, Depth Seach, and Random Walk. The reader can refer to [55] for guidance in this task.…”
Section: Stage 3: Graph Miningmentioning
confidence: 99%
“…According to the authors, experimental VR training showed favorable effects, but no evidence for that statement has been produced in the paper. A VR environment of a ship deck was developed using the Unity 3D game engine, a popular software framework designed for the development of video games [45]. The extension of this study by the same group of authors, however, offered a fully immersive experience of the firefighting training on the ship using wearable technology [46].…”
Section: Use Of Vr In Maritime Firefighting Trainingmentioning
confidence: 99%